Features of triple-negative breast cancer: Analysis of 38, 813 cases from the national cancer database. Issue 35 (August 2016) - Plasilova, Magdalena L.; Hayse, Brandon; Killelea, Brigid K.; Horowitz, Nina R.; Chagpar, Anees B.; Lannin, Donald R.
Abstract : Abstract: The aim of this study was to determine the features of triple-negative breast cancer (TNBC) using a large national database. TNBC is known to be an aggressive subtype, but national epidemiologic data are sparse. All patients with invasive breast cancer and known molecular subtype diagnosed in 2010 to 2011 were identified from the National Cancer Data Base (NCDB). Patients with and without TNBC were compared with respect to their sociodemographic and clinicopathologic features. TNBC was present in 38, 628 of 295, 801 (13%) female patients compared to 185 of 3136 (6%) male patients ( P < 0.001). The incidence of TNBC varied by region from 10.8% in New England to 15.8% in the east south central US ( P < 0.001), as well as by race with the highest rates in African-Americans (23.7%), and lowest in Filipino patients (8.9%). The incidence of TNBC also varied by histology, accounting for 76% of metaplastic cancers, but only 2% of infiltrating lobular carcinomas. TNBCs were significantly larger than non-TNBC (mean 2.8 cm vs 2.1 cm, P < 0.001), and more TNBC were poorly differentiated compared to other subtypes (79.7% vs 25.8%, P < 0.001). On univariate analysis, TNBC was no more likely than non-TNBC to have node-positive disease (32.0% vs 31.7%, respectively, P = 0.218) but in a multivariable analysis controlling for tumor size and grade, TNBC was associated with significantly less node-positivity (OR = 0.59; 95% confidence interval [CI]: 0.57–0.60). TNBC has distinct features regarding age, gender, geographic, and racial distribution. Compared to non-TNBC, TNBC is larger and higher grade, but less likely to have lymph node metastases.